Implementasi Pemberian Pinjaman Modal Kerja bagi Industri Kecil dan Pedagang Kecil di Kabupaten Bojonegoro - Indah Ratna Sari (Jurnal Administrasi Publik, 2014)
Abstract: Implementation Working Capital Lending to Small Industries and Small Trades of Bojonegoro Regency. Small industries and small trades have a strategic role in realizing economic development but it can also increase people’s income. Constraints faced by small industries and small traders in Bojonegoro regency generally in the capital. The purpose of this study is to investigate the implementation of the provision of working capital loans for small industrial entrepreneurs and small traders.This research used descriptive method using qualitative approac. The result of this study proved that the implementation of working capital lending to small industries and small traders was properly done according to Mayor Regulation number 13 year 2012 the technical team as the technical executor has conducted socialitation, field survey, group target determination, and tending ceilling determination. Bank jatim as the main executor also has completed its duly fits to the right and obligation. Keywords: implementation, small business, working capital Abstrak: Implementasi Pemberian Pinjaman Modal Kerja bagi Industri Kecil dan Pedagang Kecil di Kabupaten Bojonegoro. Industri kecil dan pedagang kecil memiliki peran yang strategis dalam mewujudkan pembangunan ekonomi selain itu dapat meningkatkan pendapatan masyarakat. Kendala yang dihadapi oleh industri kecil dan pedagang kecil di Kabupaten Bojonegoro secara umum yaitu pada permodalan. Tujuan penelitian ini untuk mengetahui implementasi pemberian pinjaman modal kerja bagi industri kecil dan pedagang kecil. Metode penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif. Hasil penelitian ini menunjukkan bahwa implementasi pemberian pinjaman modal kerja bagi industri kecil dan pedagang kecil telah berjalan dengan baik sesuai dengan Perbup Nomor 13 tahun 2012. Tim teknis sebagai implementor telah melaksanakan sosialisasi, survey lapangan, penentuan target grup dan penentuan plafon pinjaman. Bank jatim sebagai bank pelaksana juga telah melaksanakan tugasnya sesuai dengan hak dan kewajibannya. Kata kunci: implementasi, usaha kecil, modal kerja